Stomatal Responses to Light, CO2, and Mesophyll Tissue in Vicia faba and Kalanchoë fedtschenkoi - Santos, Mauro G.; Davey, Phillip A.; Hofmann, Tanja A.; Borland, Anne; Hartwell, James; Lawson, Tracy (Frontiers in Plant Science, 2021)
The responses of stomatal aperture to light intensity and CO2 concentration were studied in both Vicia faba (C3) and Kalanchoë fedtschenkoi (Crassulacean acid metabolism; CAM), in material sampled from both light and dark periods. Direct comparison was made between intact leaf segments, epidermises grafted onto exposed mesophyll, and isolated epidermal peels, including transplantations between species and between diel periods. We reported the stomatal opening in response to darkness in isolated CAM peels from the light period, but not from the dark. Furthermore, we showed that C3 mesophyll has stimulated CAM stomata in transplanted peels to behave as C3 in response to light and CO2. By using peels and mesophyll from plants sampled in the dark and the light period, we provided clear evidence that CAM stomata behaved differently from C3. This might be linked to stored metabolites/ions and signalling pathway components within the guard cells, and/or a mesophyll-derived signal. Overall, our results provided evidence for both the involvement of guard cell metabolism and mesophyll signals in stomatal responses in both C3 and CAM species.